Is An Introduction of Derivatives Trading Cause-Increased Volatility? - Joshipura, Mayank (Indian Journal of Finance, 2010)
As the word suggests, derivative is a financial contract, which derives its value from its underlying variable. The variable can be any asset, index, interest rate, weather and so on. Derivatives provide a platform to the participants for hedging their real or potential exposure, speculating on the degree and the direction of the movement in underlying variable and finding and exploiting arbitrage opportunities arising out of temporary mispricing of various derivative products or the temporary violation of non arbitrage conditions between derivative contract and its underlying variable from which it derives value. The major attraction of the derivative market for the traders is that it allows them to assume highly leveraged positions at low transaction costs and also allows them to crate some of the highly flexible and innovative payoffs by combining different derivatives products.